Science Teaching and Teacher Training: The Child and Scientific Literacy (Research, Society and Development, 2019)
This article presents a bibliographical review, with a qualitative approach and documentary character, about the following problem: "Is there a relation between the teaching of science for the initial years and the training of teachers in the area of natural sciences?". It reflects on the contingencies that produced the process of schooling in the formation of teachers who work in the initial years, in this case the Pedagogues, teaching Natural Sciences for children. It is perceived that there is an emerging and growing concern with the directions that the Natural Sciences area has faced in the early years of Elementary Education, in the sense that the Teaching of Science in the historical process was thought by adults, which as a result may have left the power of the sensitive and the imaginary of the child. This is very important for the child to perceive in the world, thinking and acting guided by the significant knowledge of the Natural Sciences. Whereas the teaching of Science for the initial years requires the planning of strategies by the educator and this production of educational strategies goes beyond the application of scientific methods and the preparation of lesson plans. Therefore, it is necessary to be involved in overcoming the existing gaps in the training and approach of knowledge made in Higher Education and what is presented to children in the classroom.